Embryological developmental changes in the gonads of male mice associated with lead administration - Ibtisam J. Sodani; Basima M. Al-Juboori (مجلة بغداد للعلوم, 2024)
The biological systems of human in the modern world are increasely being exposed to lead which exists in the environment. Women at reproductive age and pregnant are more susceptible to the danger of environmental lead pollutant leading to infertility. Prenatal exposure to lead may cause abnormal growth, spontaneous abortion and congenital problems. As there is an increase usage of electrical generators that depend on lead-based gasoline by Iraqi people which lead to increase the air pollution with this toxic substance induced us to detect through this study its possible negative effects on the fate of conception and embryonic development using the mouse as a model. The study aims to asses the effect of low dose concentrations of lead acetate given to pregnant female mice on the development of gonads of male mice embryos at different periods of gestation. Mature mice aging 8-10 weeks(180 mice) weighing 25-27 grams were used. The animals were divided into three major experimental groups (G1, G2, G3)according to the level of the dose (30 animals/ group), paralleled with three control groups(C1, C2, C3). Each major group subdivided into three minor groups(10 animals/ group) according to different periods for sacrificing during gestation period (day 14, day17, and day 20). Vaginal smears were taken from all animals daily until metestrus phase and mating was occurred using one male mouse for each female, the first day of pregnancy registered, indicated by presence of vaginal pluge. Experimental groups G1, G2 and G3 administrated daily with either 0.1, 0.2 or 0.4 mg/kg body weight of lead acetate respectively dissolved in normal saline, injected intraperitoneally for 14, 17 or 20 days of gestation, while corresponding   control animals C1, C2 and C3 were injected with normal saline only with doses and periods similar to that used with experimental animals. Mother's body weight, weight of uterus, weight and  numbers of fetuses in right and left horn, pregnancy outcomes (abortion, and stillbirth), and diameter of fetal testes were recorded after 14, 17, and 20 day post coitum (dpc). Results showed a significant decrease in all the studied parameters of the experimental groups including: mother’s body weights, uterus weights, numbers and weights of fetuses, pregnancy outcomes (abortion and stillbirth) and diameter of fetal testes compared to that of the control groups. Histological study showed significant increase in the diameter of the testis at age 14 days with the low dose, then it become significant decrease at age 17 and 20 days of gestation with disrupting of testicular structure organization, degeneration of germ cells and absence of basal lamina in all the experimental groups. In additon undescending of the testes to its normal position was observed in all experimental groups at 17 and 20 dpc. It remained adjacent to the kidneys at the upper part of the abdominal cavity while it was normally relocating at the base of the abdominal cavity in control groups at 17 dpc and descent into inguinal canal at 20 dpc. It was concluded from these results that lead acetate given to pregnant female mice impaired the gonads of male mice embryos with reduction in mother's body and uterus weights along with adverse pregnancy outcomes. These negative effects induced us to avoid the dangerous from using this toxic substance and trying to found effective alterative materials through environmental safety centers